Tale of two hearts: a TNNT2 hypertrophic cardiomyopathy case report - Pham, Justin H.; Giudicessi, John R.; Tweet, Marysia S.; Boucher, Lauren; Newman, D. Brian; Geske, Jeffrey B. (Frontiers in Cardiovascular Medicine, 2023)
Hypertrophic cardiomyopathy (HCM) is a heritable cardiomyopathy that is predominantly caused by pathogenic mutations in sarcomeric proteins. Here we report two individuals, a mother and her daughter, both heterozygous carriers of the same HCM-causing mutation in cardiac Troponin T (TNNT2). Despite sharing an identical pathogenic variant, the two individuals had very different manifestations of the disease. While one patient presented with sudden cardiac death, recurrent tachyarrhythmia, and findings of massive left ventricular hypertrophy, the other patient manifested with extensive abnormal myocardial delayed enhancement despite normal ventricular wall thickness and has remained relatively asymptomatic. Recognition of the marked incomplete penetrance and variable expressivity possible in a single TNNT2-positive family has potential to guide HCM patient care.